APPLYING DESIGN ALTERNATIVE APPROACH TO OPTIMIZE COMFORT, SAFETY, AND COST-EFFECTIVENESS IN THE REDESIGN OF ACCOMMODATION ROOMS ON THE SHIP KM TAREX 2 - Mustain, Achmad Difa Khoirul; Wahidin, Aang; Soelistijono, Rachmad Tri; Nugroho, Priyambodo Nur Ardi; Ashari, Azza Nuha Salma (Journal of Marine-Earth Science and Technology, 2024)
In late December 2021, the ship KM Tarex 2, owned by PT. Pelayaran Mandala Sejahtera Abadi, underwent its annual docking at PT. Tambangan Permai Raya. During this time, the ship was found to be in a state of disrepair, including its accommodation rooms. The ship's current condition, feedback from stakeholders, and financial considerations served as the catalyst for a comprehensive interior redesign, with a primary focus on enhancing comfort, safety, and economy. The interior redesign of the accommodation spaces on the ship KM Tarex 2 involved the exploration of two alternative design concepts. These concepts centered around the Owner's Room, Crew's Room, Messroom and Life Jacket Storage. Alternative Design 1 adopted a Contemporary Concept, while Alternative Design 2 embraced a Modern Minimalist concept. The selection process for these designs involved soliciting feedback from a panel of 18 individuals, consisting of 12 representatives from PT. Pelayaran Mandala Sejahtera Abadi, 3 individuals from PT. Tambangan Permai Raya, and 3 crew members of the ship KM Tarex 2. Ultimately, Alternative Design 1 garnered an average approval rating of 67% across all rooms, surpassing Alternative Design 2 in preference. The selected design alternatives were evaluated for compliance with regulatory standards, achieving a 100% compliance rate for each room and an average comfort rating of 40%. Additionally, the chosen materials, as determined through a Google Form questionnaire, included ALUMETAL brand ACP Materials for room lining and ceiling, along with Henan Fortovan brand LVT for ship deck covering. These materials received an average approval rating of 61%. Economically, the analysis of material costs demonstrated that the project could be undertaken without exceeding the ship's annual income, ensuring financial feasibility.